The Effect of Religiusity, Profit and Loss Sharing, and Promotion on Consumer Intention to Financing in Islamic Bank toward Trust as an Intervening Variable - Rizal Ula Ananta Fauzi; Afriansyah Saputra; Isabelaindah Puspita Ningrum (Jurnal Ilmiah Ekonomi Islam, 2022)
The purpose of this study was to determine the effect of Religiosity, perception of profit-sharing, and promotion on public interest in Islamic bank financing with trust as an intervening variable. The research sample is 384 respondents. The research method used is a quantitative approach with multiple regression analysis and Sobel Test using the help of the IBM SPSS Version 26 program. The results of this study are that Religiosity has no significant effect on interest in financing, while perceptions of profit sharing and promotions have a significant effect on interest in financing. Religiosity, perception of profit-sharing, and promotion significantly affect trust. Directly trust has a significant effect on interest in financing. From the results of the Sobel test, it was found that Religiosity, perception of profit-sharing, and promotion had a significant effect on interest in financing with trust as a mediation.